A kinetic study of La0.75Sr0.25Cr0.5Mn0.5O3-δ nano-structured electrodes for intermediate temperature symmetric solid oxide fuel cells - Montenegro Hernández, Alejandra (2023)
La0.75Sr0.25Cr0.5Mn0.5O3-δ (LSCM) mixed conducting has been studied as nanostructured air and fuel electrode, for intermediate temperature symmetric Solid Oxide Fuel cell (S–SOFC). The possible mechanisms involved in the oxygen reduction and hydrogen oxidation reactions of these LSCM nanostructures porous electrodes deposited on La0.8Sr0.2Ga0.8Mg0.2O3-δ (LSGM) electrolyte, were analyzed by electrochemical impedance spectroscopy (EIS) at 700 °C varying the oxygen partial pressure (pO2) and the hydrogen partial pressure (pH2). This analysis was complemented by the study of the electrical conductivity by the four-probe DC technique in the range between 300 and 800 °C in flowing dry atmospheres of air or H2. Results suggested that the O2 reduction reaction mechanism involves the O2- dissociative adsorption and O- ion migration near the surface region, while the H2-oxidation reaction limiting-step is controlled by a slow charge transfer process, and H2- dissociative adsorption on the ultimate O-layer.